Species Composition of Uropathogens and Sensitivity Range to Antibiotics of the Main Pathogens Isolated from the Urine of Patients with Urolithiasis - E. I. Vasilyeva; V. I. Sokolova; D. A. Sychev; M. B. Babarina (Антибиотики и Химиотерапия, 2020)
4324 patients with a basic diagnosis of urolithiasis were examined from 2010 to 2015. 2372 strains were isolated, the leading uropathogens were the bacteria of the genus Enterococcus and Escherichia coii. The high activity of phosphomycin against both gram-positive and gram-negative cultures was noted, which makes it possible to recommend this drug as prophylaxis, in particular for endoscopic procedures. Because of the high resistance of most uropathogens (29% and more), as well as the possible selection of multiresistant pathogens, fluoroquinolones should not be routinely prescribed and should be used in the presence of confirmed sensitivity to them, as well as for suspected infections of the upper urinary tract.